Work Hours Constraints and Health - David Bell; Steffen Otterbach; Alfonso Sousa-Poza (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
The issue of whether employees who work more hours than they want to suffer adverse health consequences is important not only at the individual level but also for governmental formation of work time policy. Our study investigates this question by analyzing the impact of the discrepancy between actual and desired work hours on self-perceived health outcomes in Germany and the United Kingdom. Based on nationally representative longitudinal data, our results show that work-hour mismatches (i.e., differences between actual and desired hours) have negative effects on workers health. In particular, we show that "overemployment" - working more hours than desired - has negative effects on different measures of self-perceived health.
Keywords: I10; J21; J22; 330; Work time; hours constraints; health; Germany; United Kingdom; Arbeitszeit; Überbeschäftigung; Gesundheit; Wahrnehmung; Deutschland; Großbritannien